Genome-wide interaction study of dust mite allergen on lung function in children with asthma - Forno, Erick (J Allergy Clin Immunol, 2017)
BACKGROUND: Childhood asthma is likely the result of gene-by-environment (G×E) interactions. Dust mite is a known risk factor for asthma morbidity. Yet, there have been no genome-wide G×E studies of dust mite allergen on asthma-related phenotypes. OBJECTIVE: To identify genetic variants whose effects on lung function in children with asthma are modified by level of dust mite allergen exposure. METHODS: A genome-wide interaction analysis of dust mite allergen level and lung function was performed in a cohort of Puerto Rican children with asthma (PRGOAL). Replication was attempted in two independent cohorts, the Childhood Asthma Management Program (CAMP) and the Genetics of Asthma in Costa Rica Study. RESULTS: SNP rs117902240 showed a significant interaction with dust mite allergen level on FEV(1) in PRGOAL (interaction P=3.1×10(−8)), and replicated in the same direction in CAMP White children and CAMP Hispanic children (combined interaction P=0.0065 for replication cohorts and 7.4×10(−9) for all cohorts). Rs117902240 was positively associated with FEV(1) in children exposed to low dust mite allergen levels, but negatively associated with FEV(1) in children exposed to high levels. This SNP is on chromosome 8q24, adjacent to a binding site for CEBPβ, a transcription factor that forms part of the IL-17 signaling pathway. None of the SNPs identified for FEV(1)/FVC replicated in the independent cohorts. CONCLUSIONS: Dust mite allergen exposure modifies the estimated effect of rs117902240 on FEV(1) in children with asthma. Analysis of existing data suggests this SNP may have transcription factor regulatory functions.